DO TEACHERS GIVE DIAGNOSTIC ASSESSMENT TO MEASURE STUDENTS’ MISCONCEPTION? - Nusantara, Bayuk; Nusantara, By Tri Agung; Misbah, Fathir Husain (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2023)
The importance of diagnostic assessment should be realized by teachers. This paper presents the results of a qualitative study on teachers’ perspective about diagnostic assessment. Teachers were interviewed about their perspective regarding the importance of giving diagnostic assessment to measure students’ misconception and also the implementation of diagnostic assessment. The result showed that the teacher only diagnosed students’ ability not giving the a diagnostic test to measure misconception. Thus, the government can give socialization about diagnostic testing to the teachers so that teachers will be more aware in utilizing diagnostic testing to measure students’ misconception.